Pilkada DKI Jakarta 2017: Dinamika Politik Identitas di Indonesia - Dina Lestari (Universitas Trunojoyo Madura, 2019)
Regional Election is one of implementation of people sovereignty that carried out directly, publicly, freely, confidentially, honestly and fairly. But regional election is often colored by identity politics in achieving pragmatic goals such as in the DKI Jakarta Election 2017. This study using a qualitative approach which is a contextual research that seeks to emphasize the meaning of a phenomenon of human behavior interactions in certain situations. This paper aims to find out about the 2017 DKI Jakarta regional election: the political identity dynamics in Indonesia. The results of this study are expected to provide input to relevant stakeholders to prevent the spread of identity politics in Indonesia.